2018
DOI: 10.1073/pnas.1716252115
|View full text |Cite
|
Sign up to set email alerts
|

Systematic mapping of free energy landscapes of a growing filamin domain during biosynthesis

Abstract: SignificanceEfficient synthesis and folding of proteins, avoiding misfolded states, are central to cell function. As folding may be initiated in parallel with translation, key experimental challenges are to map changes that occur in folding free energy landscapes as translation proceeds and to understand how these landscapes might be modulated by the ribosome and auxiliary factors. Here, we study the length-dependent folding of a domain from a tandem repeat protein and solve the structure of a stable folding i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
79
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
3
2

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(80 citation statements)
references
References 29 publications
1
79
0
Order By: Relevance
“…3, together with a curve derived from the NMR data showing averaged relative intensities of three 15 N amide resonances arising from the unfolded FLN5 domain [14]. To be consistent with the published NMR data [13,14], in this case we plot the data as a function of L * , i.e., the distance between the C-terminal end of the FLN5 domain and the PTC (c.f., Fig. 1b).…”
Section: Cotranslational Folding Of the Fln5 Domainmentioning
confidence: 94%
See 2 more Smart Citations
“…3, together with a curve derived from the NMR data showing averaged relative intensities of three 15 N amide resonances arising from the unfolded FLN5 domain [14]. To be consistent with the published NMR data [13,14], in this case we plot the data as a function of L * , i.e., the distance between the C-terminal end of the FLN5 domain and the PTC (c.f., Fig. 1b).…”
Section: Cotranslational Folding Of the Fln5 Domainmentioning
confidence: 94%
“…The cotranslational folding of the Ig-like FLN5 filamin domain has previously been studied by NMR measurements on ribosome-attached nascent chains and of purified C-terminally truncated versions of the protein [13,14]. The main conclusion from these studies is that FLN5 folds only when it has fully cleared the exit tunnel and is some distance away from the ribosome surface, at a tether length of 40-45 residues.…”
Section: Cotranslational Folding Of the Fln5 Domainmentioning
confidence: 99%
See 1 more Smart Citation
“…We have validated our new experiment, which we term the SOFAST-H(Z/D)QC, by comparison with 1 H, 15 N SOFAST-HMQC measurements of the folded protein ubiquitin, and the unfolded Y719E variant of the FLN5 filamin domain 36,37 . Analysis of the integrated amide signal intensity as a function of the inter-scan delay showed that for both samples the sensitivity of SOFAST-HZQC and SOFAST-HDQC experiments was very close to the expected factor of √ 2 less than the SOFAST-HMQC (Fig.…”
Section: /19mentioning
confidence: 99%
“…It is critical, therefore, that this initial folding event proceeds with fidelity and avoids toxic misfolded states (1,2). Both the vectorial nature of translation and interactions with the ribosome can affect this process (3)(4)(5)(6)(7)(8), such that the co-translational folding pathway can be different from the pathway observed during re-folding experiments. For instance, co-translational folding of firefly luciferase promotes formation of an intermediate that helps to prevent misfolding (9).…”
Section: Introductionmentioning
confidence: 99%